Halal Friendly Attribute of Muslim Travellers Toward A Non-Muslim Destination - Ghea Putri Aliffia; Rita Komaladewi (Islamic University of Kalimantan MAB Banjarmasin, 2021)
Halal tourism is a new phenomena of the growth of the halal industry. The demand for halal products and services has also increased, both in tourist destinations obtained by having Muslim and non-Muslim populations. Muslim tourists have unique needs when traveling, especially if there is a tourist destination with a large population of non-Muslims. This study aims to determine the preferences of Muslim travelers through the analysis of halal friendly attributes on non-Muslim travel destinations. The sampling technique uses unknown population with a total sample of 100 respondents and the sampling technique uses purposive sampling (domestic travelers and a Muslim who have visited Bali tourism destination at least one time) Data analysis techniques in this study used qualitative, analysis techniques with factor analysis. Factor analysis is used to identify an important set of variables from a set of variables that are more numerous to be used in subsequent multivariate analysis. The results of this study indicate that Muslim travelers preferences based on halal friendly attributes in non-Muslim travel destinations of the most dominant attributes considered important are good of quality halal food and drinks as well as the availability of information about halal in the travel area. These attributes can be the main focus of attention for tourism service providers in order to improve the quality of Muslim-friendly tourism in Bali.Keywords: preferences, halal tourism, muslim travelers, non-muslim travel destinations